The clinical case of limb-girdle muscle dystrophy 2Q associated with myasthenic syndrome and lung damage - S. N. Bardakov; R. V. Deev; M. O. Mavlikeev; Z. R. Umakhanova; P. G. Akhmedova; R. M. Magomedova; K. Z. Zulfugarov; V. A. Tsargush; I. A. Chekmareva; I. A. Yakovlev; G. D. Dalgatov; G. I. Yakubovsky; et al. (Нервно-мышечные болезни)
Limb-girdle muscle dystrophy 2Q is one of the rarest forms of plectinopathies and is represented by an isolated muscular dystrophic syndrome, according to two previously described literature reports. There are five forms of plectinopathies, including limb-girdle muscle dystrophy 2Q, are caused by mutations in the PLEC gene, the alternative splicing of which determines the synthesis of 9 isoforms of the plectin protein (1, 1a, 1b, 1c, 1d, 1e, 1f, 1g, 3) performing cytolinker function in the neuronal, epithelial and muscle tissue.The article describes the family observation of three sick siblings with the limb-girdle muscle dystrophy 2Q phenotype due to the presence of a new homozygous mutation (NM_201378.3:c.58G>T, NP_958780.1:p.Glu20Ter) in the isoform 1f PLEC revealed by whole-exome sequencing. Clinical, electromyography, visualization and histopathological features of limb-girdle muscle dystrophy 2Q were analyzed in detail. The onset of clinical manifestations in all the described siblings was observed in early childhood with moderate weakness mainly in the pelvic girdle muscles and proximal lower limbs with minimal involvement of the muscles of the shoulder girdle. A distinctive aspect is the stagnation of the myodystrophic process until 20—21 years, followed by the progression and development of episodes of respiratory failure, as well as the formation of rigidity of the cervical, thoracic spine and moderate contracture of the Achilles tendons. Typical features are marked atrophy of paravertebral muscles with the formation of pterygoid scapula and the presence of hypertrophy m. gastrocnemius, m. quadriceps femoris, m. deltoideus and m. triceps brachii. Histopathological examination m. vastus lateralis revealed myodystrophic process without inflammatory infiltration, muscle fiber cytoskeleton disorganization resulted from the plectin loss.Electrocardiography signs of the early repolarization syndrome, focal cardiosclerosis and sinus tachycardia are described. For the first time, involvement in the pathological process of pulmonary tissue in the form of noninfectious bronchiolitis, atelectasis, and the development of the myasthenic syndrome causing episodes of respiratory failure resulted in the death of two described siblings aged 29 and 31 years. Discussed pathogenetic role of PLEC 1f isoform in the development of described syndromes, expands understanding of rare nosology limb-girdle muscle dystrophy 2Q.